Lithium‐Aluminate‐Catalyzed Hydrophosphination Applications. (25th July 2019) - Pollard, Victoria A.; Young, Allan; McLellan, Ross; Kennedy, Alan R.; Tuttle, Tell; Mulvey, Robert E.
Abstract: Synthesized, isolated, and characterized by X‐ray crystallography and NMR spectroscopic studies, lithium phosphidoaluminate iBu3 AlPPh2 Li(THF)3 has been tested as a catalyst for hydrophosphination of alkynes, alkenes, and carbodiimides. Based on the collective evidence of stoichiometric reactions, NMR monitoring studies, kinetic analysis, and DFT calculations, a mechanism involving deprotonation, alkyne insertion, and protonolysis is proposed for the [iBu3 AlHLi]2 aluminate catalyzed hydrophosphination of alkynes with diphenylphosphine. This study enhances further the development of transition‐metal‐free, atom‐economical homogeneous catalysis using common sustainable main‐group metals. Abstract : Al‐ternative : Für die katalytische Hydrophosphinierung ungesättigter organischer Substrate werden üblicherweise Übergangsmetalle herangezogen. Nun wurde gefunden, dass Aluminium ein vielversprechender Katalysator ist.